PERAN WORLD TRADE ORGANIZATION (WTO) DALAM MENYELESAIKAN SENGKETA PERDAGANGAN TIONGKOK DAN AUSTRALIA TENTANG PENERAPAN BEA ANTI-DUMPING PADA ANGGUR MERAH (WINE) DS602 - Melda Okta Shella; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The WTO's role in resolving the trade dispute between China and Australia regarding the imposition of anti-dumping duties on Australian red wine products (DS602). The dispute arose from China's policy of imposing anti-dumping duties on Australian wine imports, citing dumping and subsidy practices that were detrimental to China's domestic industry. Australia then challenged the policy at the WTO, arguing that it violated the provisions of the Anti-Dumping Agreement and the Dispute Settlement Agreement (DSU). The outcome of this dispute resolution is in accordance with Article 3.6 of the DSU, namely through a mutually agreed solution, which provides an opportunity for both countries to resolve the dispute amicably outside the WTO panel's decision while maintaining the applicable regulatory provisions.The results of this dispute resolution are in accordance with Article 3.6 of the DSB, namely through a mutually agreed solution, which provides both countries with the opportunity to resolve the dispute peacefully outside the WTO panel's decision while maintaining the applicable regulatory provisions. Keywords: WTO, Wine, Anti-dumping,Tiongkok,Australia